Maximizing Science Learning in Elementary Students: Guided Inquiry Unleashed: Potensi Terungkap: Pembelajaran Inquiry Terbimbing Meningkatkan Hasil Belajar Sains pada Siswa Sekolah Dasar - Irma Rizky Amalia; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2023)
This experimental quantitative study investigates the impact of guided inquiry learning on the learning outcomes of students in class VA at SDN Katerungan Krian. Employing a pre-experimental design with a one-group pretest-posttest approach, the research aims to describe and analyze the level of influence of guided inquiry learning. The study population comprises 30 students, and the instrument utilized is a student learning outcomes test sheet. The calculated t-value of 10.624 exceeds the critical t-value of 2.048, signifying a significant influence. Furthermore, the eta squared test yields a value of 0.068, suggesting a moderate effect size (η² = 0.119). Consequently, it can be concluded that the guided inquiry learning model significantly impacts the science learning outcomes of class VA students. These findings have important implications for science education, emphasizing the efficacy of guided inquiry methods in enhancing student learning outcomes. Highlights: Guided inquiry learning positively influences student learning outcomes in science. Experimental quantitative research design reveals the impact of guided inquiry learning on student performance. The findings emphasize the importance of incorporating guided inquiry methods in elementary science education. Keywords: Guided inquiry learning, student learning outcomes, experimental quantitative research, science education, elementary students.